2017
DOI: 10.1093/neuros/nyx001
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Pre- and Postoperative Seizures in 1033 Patients Undergoing Supratentorial Meningioma Resection

Abstract: BACKGROUND Risk factors for pre- and postoperative seizures in supratentorial meningiomas are understudied compared to other brain tumors. OBJECTIVE To report seizure frequency and identify factors associated with pre- and postoperative seizures in a large single-center population study of patients undergoing resection of supratentorial meningioma. METHODS Retrospective chart review of 1033 subjects undergoing resection of supratentorial meningioma at the author’s institution (1991–2014). Multivariate regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
92
4
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 27 publications
(27 reference statements)
11
92
4
10
Order By: Relevance
“…Correspondingly, seizures were more common in patients with a high-grade than in those with a benign meningioma. Moreover, as expected from previous series results, 4,6,12,23 rising edema and tumor volumes were positively correlated in univariate tests with an increasing incidence of preoperative seizures. However, in multivariate analyses, only increasing tumor volume (but not edema volume) remained significantly correlated with the incidence of preoperative seizures.…”
Section: Brain Invasion and The Risk Of Preoperative Seizuressupporting
confidence: 88%
See 3 more Smart Citations
“…Correspondingly, seizures were more common in patients with a high-grade than in those with a benign meningioma. Moreover, as expected from previous series results, 4,6,12,23 rising edema and tumor volumes were positively correlated in univariate tests with an increasing incidence of preoperative seizures. However, in multivariate analyses, only increasing tumor volume (but not edema volume) remained significantly correlated with the incidence of preoperative seizures.…”
Section: Brain Invasion and The Risk Of Preoperative Seizuressupporting
confidence: 88%
“…Moreover, Mantle et al 11 reported a strong association between brain-invasive growth and PTBE, which is one of the main risk factors for the development of perioperative seizures. 4,6,12,23 In the same series, the authors found a 20% increase in the incidence of brain invasion with each 1-cm increase in edema. 11 Disruption of cortical integrity by infiltrating meningioma cells with subsequent astrocytic response 24 might also impair neurological function and contribute to an increased risk of seizures in patients with brain-invasive meningioma.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Patients suffering from intracranial meningioma may be diagnosed incidentally from nonspecific symptoms such as headaches or seizures. Depending on localization, size, and peritumoral edema, meningioma patients may display specific focal neurologic deficits (Englot et al, ; Chen et al, ; Hendrix et al, , ; Wu et al, ). Olfactory groove meningiomas (OGMs) represent the prototypical meningioma lesion causing olfactory dysfunction.…”
Section: Introductionmentioning
confidence: 99%